The Educational Potential of Art and its Realization in the Context of Globalization - Shomurod Mustafayev; Kuvandyk Aitbayevich Kadyrov (Researchparks Publishing, 2022)
The article examines the place and role of art in the conditions of cultural globalization, the problem of realizing the educational potential of art. The functional capabilities and prospects for the development of the aesthetic culture of the individual are determined, including in the process of interaction of cultures of different peoples. Special attention is paid to the formation of the artistic culture of youth.